2018
DOI: 10.1186/s12891-018-2007-9
|View full text |Cite
|
Sign up to set email alerts
|

Above-versus below-elbow casting for conservative treatment of distal radius fractures: a randomized controlled trial and study protocol

Abstract: BackgroundA variety of cast options are available for the non-surgical treatment of distal radius fractures (DRF) in adults. However, the literature is inconclusive regarding the need to immobilize the elbow joint after reduction in order to prevent rotation of the forearm in order to maintain the reduction of DRF. This study aimed to evaluate the best method of immobilization between above-elbow (AE) and below-elbow (BE) cast groups at the end of six-month follow-up.MethodsThis is a randomized clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Our study strengths are: 1) an a priori protocol [ 21 ] and registration; 2) the only RCT that uses DASH as the primary outcome throughout treatment; 3) a reasonable sample size; 4) low follow-up losses; 5) broad inclusion criteria (stable and unstable fractures); 6) inclusion of functional and surrogate outcomes (PRWE, ROM, radiographical measures, VAS); 7) blinded assessments; and 8) external, public funding (no COI from industry). Study limitations include: 1) consideration of both extra-articular and intra-articular fractures together; 2) the possible need for longer follow-up to assess articular degenerative disease; 3) non-everyday methods for fracture reductions were performed in the operating room; 4) our results may not be applicable for young, active adults; 5) this was a single-center study; and 6) change of the primary outcome during recruitment phase in relation to the published protocol and registration of the research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study strengths are: 1) an a priori protocol [ 21 ] and registration; 2) the only RCT that uses DASH as the primary outcome throughout treatment; 3) a reasonable sample size; 4) low follow-up losses; 5) broad inclusion criteria (stable and unstable fractures); 6) inclusion of functional and surrogate outcomes (PRWE, ROM, radiographical measures, VAS); 7) blinded assessments; and 8) external, public funding (no COI from industry). Study limitations include: 1) consideration of both extra-articular and intra-articular fractures together; 2) the possible need for longer follow-up to assess articular degenerative disease; 3) non-everyday methods for fracture reductions were performed in the operating room; 4) our results may not be applicable for young, active adults; 5) this was a single-center study; and 6) change of the primary outcome during recruitment phase in relation to the published protocol and registration of the research.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was under an identifier number–NCT03126175 (ClinicalTrials.gov), registered in April 2017. Publication of the protocol in March 2018 [ 21 ]. Patients were recruited between April 2018 and June 2019 and last follow-ups carried out on Dec 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most prevalent fractures in older patients is distal radius fracture, which accounts for about 17% of skeletal fractures 16,17 . Numerous studies have demonstrated that distal radius anatomic repair is important for appropriate functional outcomes [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a closed reduction followed by cast immobilisation, loss of reduction and stability can occur without being noticed until the cast is removed. If the fracture has united in a mal-aligned or un-desired orientation, it can result in poor clinical outcomes in the long-term 1 . Nonetheless, closed reduction is still the primary choice of treatment for most surgeons since it is minimally invasive, cost-effective and continues to result in good clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%